AB0048 THE EXPRESSION OF T LYMPHOCYTE SUBSETS IN PERIPHERAL BLOOD OF PATIENTS WITH AUTOIMMUNE UVEITIS AND THE SHORT-TERM EFFICACY AND SAFETY EVALUATIONS OF LOW-DOSE IL-2 COMBINED THERAPY. (2nd June 2020) - Yan, T.; Li, J.
Abstract : Background: Autoimmune uveitis is a group of inflammatory diseases that affect the uveal tract such as iris, cilia and choroid. In addition to diabetic retinopathy and age-related macular degeneration, uveitis is one of the main causes of blindness in developed countries [1] .The disease is autoimmune-mediated, and abnormal immune responses are induced by pathogenic antigens such as retinal soluble antigens and retinal interphotoreceptor retinoid-binding protein (IRBP), and autoimmune inflammation is caused by specific cytotoxic effects, immune complex responses and delayed hypersensitivity reactions.It has been found that the disorder of lymphocyte subsets, mainly due to the number and function defects of regulatory T cells (Tregs), may be involved in the development of uveitis.IL-2 is a key cytokine in T cell differentiation. As a new type of immunomodulator, IL-2 has achieved preliminary efficacy in the treatment of systemic lupus erythematosus, ankylosing spondylitis, Sjogren's syndrome and other diseases [2-4], but there is no clinical evidence of IL-2 in the treatment of autoimmune uveitis.The purpose of this study was to investigate the expression of T lymphocytes in patients with autoimmune uveitis and the effect of low dose IL-2 on their immune status. Objectives: To investigate the expression of peripheral blood lymphocyte in patients with autoimmune uveitis and evaluate the short-term efficacy and safety of low-dose IL-2 combined with methylprednisolone. Methods: A total of 108 patients with autoimmune uveitis and 93 healthy subjects who visited our hospital from January 2016 to April 2019 were collected.Twenty-three patients were treated with a low dose of IL-2 (50WIU/ day for 5 consecutive days) on the basis of conventional treatment (methylprednisolone and/or DMARDs), and the changes in the patients' condition and lymphocyte subsets were observed. The t-test of two independent samples was used when the measurement data conformed to the normal distribution and the variance was homogeneous, and Manil-Whitney rank sum test was used when the measurement data did not conform to the normal distribution. Results: Among 108 patients, 58 were males and 50 were females, with an average age of 41 + 14 years. Compared with the normal control group, total T cells, total B cells, Th cells, Ts cells, Th1 cells, Th17 cells, Th1/Th2, Th17/Treg in patients with autoimmune uveitis were higher than those in healthy control group (P < 0.05), while Th1 cells and Treg cells were lower than those in healthy control group (P < 0.05). After IL-2 treatment, the number of Treg cells increased from 21.90±15.29 /ul to 51.54±41.86 /ul (P < 0.05), the Th17/Treg ratio decreased back from 0.44±0.27 to 0.33±0.23 (P < 0.05), and both serum sedimentation rate and CRP decreased compared with before treatment (P < 0.05). Conclusion: Treg cells are involved in the pathogenesis of autoimmune uveitis. Low dose of IL-2 selectively elevates Treg cells, regulates Th17/Treg balance and improves the condition of the disease. References: [1]Durrani OM, Meads CA, Murray PIJO. Uveitis: A Potentially Blinding Disease[J]. 2004, 218(4): 223-236. [2]He J, Zhang X, Wei Y, et al. Low-dose interleukin-2 treatment selectively modulates CD4(+) T cell subsets in patients with systemic lupus erythematosus[J]. 2016, 22(9): 991-993. [3]An H, Li X, Li F, et al. The absolute counts of peripheral T lymphocyte subsets in patient with ankylosing spondylitis and the effect of low-dose interleukin-2[J]. 2019, 98(15): e15094. [4]Miao M, Hao Z, Guo Y, et al. Short-term and low-dose IL-2 therapy restores the Th17/Treg balance in the peripheral blood of patients with primary Sjögren's syndrome[J]. 2018: annrheumdis-2018-213036. Disclosure of Interests: None declared